(untitled) (World Economics and Finance Bulletin, 2022)
There is no difference in the importance of the banking sector in development, which prompts countries to raise the contribution of the banking sector to the development pro- cess. Given the importance of this sector, Iraq moved to liberate the sector after the year 2003 and work to reform it continuously, according to the Banking Law, No. 94, for the year 2004, and the Central Bank Law No. 54 of 2004, and other legislative frameworks, which provide a legislative framework for the implementation of the market economy, in line with international standards, and enhance confidence in the banking sector. The banking sector still suffers from restrictions, some of which are regulatory, others linked to the banking sector, others linked to legislative aspects, and the other linked to the po- litical, security and economic environment in which it operates. The banking sector is still conservative and has not tended to expand banking activities, with a desire to reduce the amount of openness to risks, so some banks are limited to openness to cash credit, offset by weakness in actual electronic transactions, which links Iraq financially with the world. It is offset by the fact that there is a weakness in banking awareness; for this, we find that the customer base of Iraqi banks is still limited, and the size of the cash block outside the banking system is still very large. The Central Bank adopts, from time to time, introducing reforms to the sector, with the aim of making it consistent with global developments and with development needs, but the sector still has not met the ambition to carry out development tasks